Analysis of Determinants of Stock Returns Based on Liquidity and Profitability in Manufacturing Companies Listed on the IDX for the Period 2017-2022 - Ida Ayu Putu Megawati (Lembaga Riset dan Inovasi Al-Matani, 2023)
This research is a quantitative study that aims to determine and analyze the effect of liquidity and profitability on manufacturing companies listed on the IDX for the 2017-2022 period. In business activities, of course, it is necessary to analyze the condition of the company to predict future stock prices so that expectations of high returns can be achieved. When analyzing the financial statements of a company, it can be done in various ways, one of which is by calculating the desired ratios. The research population was 26 companies with a sample of 11 companies where the method used was purposive sampling method. Utilizing secondary data types and using quantitative methods, the data will be processed using the SPSS program. Based on the results of the t test research proves that liquidity partially has a significant effect on stock returns with a significant value of 0.009 < 0.050 and tu 2.757> t el 2.02108, profitability partially has a significant effect on stock returns with a significant value of 0.009 < 0.050 and tu -2.751 < t el 2.02108. The results of the F test research prove simultaneously that liquidity and profitability have a significant effect on stock returns with a significant value of 0.036 < 0.050 and tu 2.852> t el 2.61.